STUDY OF WATER QUALITY AND POLLUTION LEVEL AT KETAPANG BEACH, PESAWARAN REGENCY, LAMPUNG - Delis, Putu Cinthia; Yuliana, Darma; Kartini, Nidya (Jurusan Perikanan dan Kelautan, 2024)
Ketapang Beach, situated in Pesawaran Regency, Lampung, is a well-known tourist spot frequented by many visitors. The beach features a pier and a boat lane used for transporting tourists to nearby islands. Additionally, the surrounding area is home to residential communities and small-scale fish farming. Despite this activity, a comprehensive analysis of the beach’s water conditions had not been conducted previously, and there is limited information available on its water quality and pollution levels. Given the extensive human activity, it is crucial to monitor the water quality regularly, as these activities can significantly impact the ecosystem. This study collected data on several physical, chemical, and biological water parameters, such as temperature, total suspended solids (TSS), pH, salinity, dissolved oxygen, biochemical oxygen demand (BOD5), ammonia, nitrite, orthophosphate, lead (Pb), and total coliform bacteria. These parameters were measured to evaluate the water quality using the Pollution Index (IP), with reference to the seawater quality standards for marine tourism and aquatic life. The findings revealed that several parameters—such as salinity, dissolved oxygen, BOD5, ammonia, orthophosphate, and lead (Pb)—exceeded the recommended thresholds. Based on the Pollution Index assessment, the waters at Ketapang Beach were classified as moderately polluted.Keywords: Ammonia, pollution index, purposive sampling, water pollution.